LITERATURE REVIEW : FAKTOR PSIKOSOSIAL YANG BERHUBUNGAN DENGAN PERILAKU HIGIENE DAN SANITASI - A.A Istri Agung Mirayani; Ni Made Utami Dwipayanti (ARCHIVE OF COMMUNITY HEALTH, 2023)
Hygiene and sanitation behavior is defined as an action or effort to improve hygiene and health through early maintenance of each individual and the environmental factors that influence it, so that the individual is protected from the threat of disease-causing germs. Poor hygiene and sanitation behavior is caused by many factors. One of the approaches that influence changes in WASH behavior is the psychosocial approach of the RANAS Model. The purpose of this study was to determine the psychosocial factors associated with hygiene and sanitation behavior. Leading databases searched through Google Scholar from 2013-2023. From 174 articles, 10 articles were identified and included in the review. Several psychosocial factors influence hygiene and sanitation behavior in the school setting: perceived risk (vulnerability), attitude factor, norm factor, ability factor (self-efficacy), and self-regulation (remembering), in the household scope: risk perception, risk factor norms, ability factors, and self-regulation, in the community sphere: perceptions of risk and norms. In addition to psychosocial factors, several studies have found that gender, education level, knowledge, waste disposal, and bathing practices have an effect on hygiene and sanitation behavior. Of the five existing psychosocial factors, norms and self-efficacy factors are the most influential factors on hygiene and sanitation behavior. Therefore, in providing interventions or programs later on hygiene and sanitation behavior, interventions related to social norms and self-efficacy can be made. Key words : Psychosocial factors, RANAS Models, Hygiene and Sanitation behavior